The optimal design and three-dimensional finite element analysis of CAD/CAM integrated roach attachment - Yun Huang; Jingrong Wang; Liqing Zhu; Liren Liu; Shanshan Gao (Heliyon, 2024)
Objectives: To investigate the effect of different designs of movable parts and prosthetic materials on the stress distribution of supporting tissues in mandibular free end dentition defects using three-dimensional finite element analysis of digital Roach attachments. Material and methods: A 3D model of a patient with Kennedy class I mandibular edentulous conditions was generated, and twelve prosthesis models were applied, combining two designs of removable parts and six types of CAD/CAM restorative materials with different elastic modulus (conventional zirconia, ultra-translucent zirconia, Polyetheretherketone (PEEK), Lithium disilicate, Nanoceramic resin, and resin composite (Paradigm MZ100, 3 M ESPE)). The stress distribution of abutment periodontal ligament, edentulousmucosa, and junction of attachment were analyzed using finite element analysis. Results: The stress value of the buccal neck of the periodontal ligament and the maximum compressive stress of the distal periodontal ligament of the design with clasp arms were higher than those without clasp arms, while the stress on the junction of attachment and the displacement of the mucosa in the edentulous area were smaller. Restorative materials with high elastic modulus, such as conventional zirconia and ultra-translucent zirconia, are recommended to be used as the fixed part of Roach attachment. Conclusion: CAD/CAM Roach attachments with clasp arms are recommended for the protection of mucosal soft tissue. Restorative materials with high elastic modulus, such as conventional zirconia and ultra-translucent zirconia, are recommended as the fixed part of Roach attachment for patients with free end defect of mandibular dentition. Clinical significance: This study provides references for the design with clasp arms and the selection of clinical fixed-movable prosthetic materials. Clinicians should consider the design of attachments and selection of appropriate manufacturing materials carefully to avoid negative impacts on patients' periodontal support tissues.